Effectiveness of Sensory Integration Stimulation Implementation in Children with ADHD (Attention Deficit Hyperactivity Disorder) - Hani Deo Prasitaningsih; Childa Kumala Azzahri; Eka Putri (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
This study aims to analyze the effectiveness of implementing sensory integration stimulation for children with ADHD (hyperactivity) aged 4-6 years at TK Tahfidzul Qur'an Al Izzah Pekayon. The research employed a qualitative approach using a case study method. The research subjects consisted of five children. Data were collected through observation, interviews, and documentation. The implementation of sensory integration stimulation was conducted over four weeks and involved the development of proprioceptive, vestibular, tactile, visual, auditory, and olfactory senses through activities tailored to the children's needs. The results indicated that sensory integration stimulation effectively improved children's motor control, body balance, focus and concentration, emotional regulation, body awareness, and self-confidence. In addition, improvements were also observed in cognitive and basic language skills, such as understanding simple concepts, responding appropriately to questions, and showing increased curiosity toward the surrounding environment. These findings align with recent research proving the effectiveness of sensory integration interventions in children with ADHD.